POLA MAKANPASIEN HIPERTENSI DENGAN GAGAL GINJAL KRONIK RAWAT INAP DI RSUP Prof.Dr.R.D.KANDOU MANADO - Rivolta G.M. Walalangi; Olfie Sahelangi (POLTEKKES KEMENKES MANADO, 2015)
In Indonesia, many people who have irregular eating patterns that lead to various diseases anddisorders of the body such as hypertension, renal, uric acid and others. This study aims to finda diet that includes the type, frequency and amount of food as well as the adequacy of nutrientshypertensive patients with chronic renal failure hospitalization in RSUP.Prof.dr.RD KandouManado.This research uses descriptive survey research with cross sectional study, conducted inJanuary 2015 in Manado Prof.dr.RDKandou BLU Hospital. The sample in this study arepatients with hypertensive chronic renal failure who are hospitalized in the department BLUProf.dr.RDKandou Manado amounting to 5 people.The results showed that the respondents who consume food items animal side dish is fish,chicken and beef, nuts and processed products are consumed tofu, tempeh, peanuts andgreen beans, the type of vegetables consumed are beans, long beans , and kale while for thetype of fruit that is consumed is the papaya and pisang.Empat respondents (80%) has afrequency of eating 3 times a day ie breakfast, lunch and dinner with a frequency of snack 2x aday and a snack respondent has a frequency of> 3 times a day. The fifth respondent portions ofthe staple diet of 200 grams, 100 grams of animal dishes, vegetable dishes 100 grams, 100grams of vegetables and fruits number of servings consumed as much as 100 grams. Threerespondents have the more energy sufficiency level (> 100%) and two of the respondents havethe kind of energy sufficiency level (90-100%). Five respondents have sufficient levels ofprotein (> 100%). Sufficient levels of fat or less three respondents (70-80%), the respondentsufficiency level of good fats (90-100%) and the respondents' level of adequacy moderate (80-90%). The level of carbohydrate (> 100%) of two of the respondents, two respondents have thesufficient levels of good carbohydrates (90-100%), and one respondent had sufficient levels ofmoderate (80-90%)